Early electroencephalography in patients with emergency room diagnoses of suspected new-onset seizures: diagnostic yield and impact on clinical decision-making - Paliwal, Prakash; Pohlmann-Eden, Bernd (Seizure, 2015)
Purpose: To assess the utility of acute electroencephalography (EEG) performed in the emergency room (ER) and its impact on subsequent management of patients with new-onset seizures. Adults who recover fully in the ER following suspected isolated new-onset seizures are usually discharged to the neurology clinic for further review. An EEG at that stage may be normal. We sought to assess the feasibility and yield of early EEG in the ER setting, its impact on management. Methods: A prospective study from January 2008 to January 2011 of patients diagnosed by ER physicians with uncomplicated suspected first episodes of unprovoked convulsive seizures. All patients underwent routine 30-min EEG in the ER prior to discharge and specialist review was arranged in the epilepsy clinic within 2 weeks of presentation. Management decisions were at the discretion of the treating neurologist. Seizure recurrence was assessed during a follow up period between 9 months and 3 years. Results: 136 patients were included in the study (92 males). Mean age was 32 years (range 16-73). Forty had abnormal EEGs: 16 focal epileptiform discharges, 12 focal slowing, 10 generalized spike-wave discharges and 2 generalized slowing. Using multivariate analysis, those with abnormal EEG (51% vs 11%, p=0.003) and abnormal MRI (53% vs 28%, p<0.001) were more likely to be commenced on anticonvulsant therapy. Abnormal MRI (p=0.001) was independently associated with a higher risk of recurrence. Conclusions: Following an ER diagnosis of new-onset uncomplicated seizure, early EEG had a high diagnostic yield. Abnormal EEG and abnormal MRI significantly contributed to decision-making regarding treatment at specialist review. Abnormal MRI was associated with significantly higher risks of subsequent seizures.